Awareness about the significance of acid-base balance of saliva in maintaining oral health - Charanya Suresh; Vishnupriya Veeraraghavan; Selvaraj Jayaraman; R Gayathri; S Kavitha (Wolters Kluwer Medknow Publications, 2022)
Saliva is a multilayered secretion. The quality of saliva is just as crucial as the quantity. Saliva is necessary for preserving the integrity of oral structures, personal connections, digestion, and acid-base balance. The acid-base balance in one's oral environment is always being challenged. It happens every time we eat a meal, and when microorganisms are present. At a pH of 5 or 5.5, the demineralization of the enamel and hard tooth structures occurs. This study aimed to raise awareness about the importance of acid-base balance of saliva in dental health. A self-structured questionnaire was prepared to assess the awareness on the importance of acid-base balance in maintaining oral health. The questionnaire consisted of 20 questions, and the results were plotted in a graph. The Chi-square test was employed for evaluating the data, which was done with SPSS software. The study indicated that 91.74% of the participants were aware of the salivary pH in case of healthy gingiva, 34.82% of the respondents were aware of the salivary pH in case of chronic gingivitis, and 20.33% of the respondents were aware of the salivary pH in case of chronic periodontitis. We also correlated our results with gender and year of study. Oral health plays a major role in identifying systemic diseases and hence enough knowledge about various aspects about the oral cavity and its manifestations needs to be created among dental students to ensure that they become efficient dental surgeons in the future. Even though a fair amount of people knew the pH of clinically healthy gingiva, most of them did not know the pH at which periodontitis or gingivitis was caused. Hence, creating awareness about this topic stands vital. Further studies are required for a better understanding of salivary components and how they affect the caries process. The utilization of modified oral molecules as medicinal agents could become a reality with this understanding. Our findings imply that being aware of dietary composition has an impact on acid-base balance. To maintain the correct acid-base balance, more awareness of protein consumption is required.